The Effect of Leadership Style and Work Discipline on Employee Performance at PT Indonesia Nippon Seiki Cikande Serang - Rima Handayani (PINISI Discretion Review, 2020)
The role of HR management in carrying out aspects of HR must be managed properly so that policies and practices can be run in accordance with what the company wants. The purpose of this study was to determine the effect of partially and simultaneously leadership style and work discipline on employee performance at PT. Indonesia Nippon Seiki Cikande Serang. And to find out how much influence the leadership style and work discipline on employee performance at PT. Indonesia Nippon Seiki Cikande Serang. The research method used is quantitative research. The population in this study were all employees at PT. Indonesia Nippon Seiki Cikande Serang. The sample used in this study was 87 respondents. Data collection techniques by questionnaire, and data analysis techniques by instrument test, correlation coefficient, multiple linear regression, coefficient of determination, classical assumption test, t-test and F-test. The results showed that partially the leadership style had a positive and significant effect on employee performance, this could be proven from the tcount of 5.992> ttable 1.988 with a significant 0.000 <0.05 then H0 was rejected and Ha was accepted, meaning that there was a positive and significant influence of leadership style on performance the employee. Partially, work discipline has a positive and significant effect on employee performance, this can be proven from the value of tcount 7.088> ttable 1.988 with a significant 0.000 <0.05, then H0 is rejected and Ha is accepted, meaning there is a positive and significant effect of work discipline on employee performance. Simultaneously leadership style and work discipline have positive and significant effect on employee performance. This can be proven from the value of Fcount 62.884> Ftable 3.11 with a significance of 0.000 <0.05, thus Ho is rejected and Ha is accepted, meaning that there is a positive and significant influence of style leadership and work discipline simultaneously on employee performance. The magnitude of the effect of leadership style and work discipline simultaneously on employee performance by 60%, while the remaining 40% is influenced by other variables not examined in this study. And the value of R (Correlation) of 0.774 means that the level of relationship between leadership style (X1) and work discipline (X2) simultaneously on employee performance (Y) has a strong relationship level.